The use of brachio-basilic arterio-venous fistulae for haemodialysis – a single centre descriptive study - Chibuye, Kenward (Division of General Surgery, 2022)
Aim: To report on our local experience with the use of brachio-basilic arteriovenous fistulae (BBAVFs) and to encourage wider local acceptance of the procedure in accordance with international guidelines. The primary aim of the study was to report on access patency, including primary, assisted-primary and secondary patency at 30 days, 1 year and 3 years. The secondary aims were to report on complications and functional outcomes with this technique. Methods: This is a retrospective, descriptive study of 41 consecutive haemodialysis patients that underwent BBAVF creation at Groote Schuur Hospital, from 1 January 2014 to 24 April 2020. Results: The median age of the patients was 45 years (IQR 32-54). Twenty females and 21 males were included in the study. Of the 41 BBAVFs that were performed, 24 (58.5%) were performed as a one-stage procedure and 17 (41.5%) as a two-stage procedure. The primary patency rates at 30 days, 1-and 3-years were 95.1% (95% CI 81.9-98.8), 48.8% (95% CI 32.9-62.9) and 19.5% (95% CI 9.2-32.7). Assisted-primary patency rates at 30 days, 1-and 3years were 100%, 67.7% (95% CI 50.0-80.1) and 24.3% (95% CI 12.1-38.8). Secondary patency rates at 30 days, 1-and 3-years were 100%, 70.3% (95% CI 52.8-82.3) and 27% (95% CI 14.1-41.8). Of the 41 patients that underwent BBAVF creation, 4 (9.8%) presented with minor complications within 30 days. The median interval from creation to use was calculated as 46 days (IQR 38-51). The median interval from BBAVF creation to catheter removal was calculated as 73 days (IQR 57-79). Conclusion: BBAVFs can successfully be performed in a resource constraint environment by surgeons with limited prior experience with the technique. However, careful monitoring, well-established referral pathways for dysfunctional fistulae and access to surgical or endovascular revision seem to be key factors in ensuring long-term patency.